2019
DOI: 10.24874/ti.2019.41.04.11
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of Internal Combustion Engine Efficiency While Introducing Additives in the Oil

Abstract: The resource of modern internal combustion engines (ICE) ranges from 200 thousand up to 1 million km. This is due to significant design changes in the ICE systems, as well as the properties of working oils and additives to them. Parts of an internal combustion engine have reached the limit of accuracy. The topical direction of extending the service life of assemblies and ICE systems is the use of various nanoparticles added to the lubricant. Ten different nanoparticles were selected for the experiment. When co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…A number of studies indicate the formation of a diamond-like carbon surface layer when introducing a serpentinite additive. It is the interaction at the carbon level that helps to reduce friction [42].…”
Section: Selection Of Research Materialsmentioning
confidence: 99%
“…A number of studies indicate the formation of a diamond-like carbon surface layer when introducing a serpentinite additive. It is the interaction at the carbon level that helps to reduce friction [42].…”
Section: Selection Of Research Materialsmentioning
confidence: 99%
“…Our analysis of the methods and means used to control exhaust systems showed that a more reliable method is needed [18]. In our case, the appropriate method is to analyse the composition of exhaust gases in individual cylinders (selectively) in test modes [17]. The essence of the method is that the gas is analysed at the points of the exhaust gas exit from each individual cylinder [22].…”
Section: Introductionmentioning
confidence: 99%
“…It is impossible to achieve meaningful progress in the areas indicated in clauses 4) and 5) without internal and external means to control the technical condition of nodes and systems [17]. The lack of control tools which can reliably determine the technical condition of ICE systems leads to high costs during troubleshooting [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our paper, we study the temperature characteristics of the lubricating oil at the outlet of the K27-145 TCR rotor bearing at various operating parameters of the TCR lubrication system. The most informative method is that based on the analysis of the characteristics of engine rundown, a TCR or any other triboconjugation operating with liquid lubrication [30]. We identify the relationship between the oil outlet temperature and the operating parameters of the TCR lubrication system.…”
Section: Introductionmentioning
confidence: 99%